PEMANFAATAN TEPUNG UBI JALAR UNGU DAN TEPUNG KULIT ARI KACANG KEDELAI DALAM PEMBUATAN FLAKES - Pehulisa, Astaria; Pato, Usman; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to determine and obtain the optimal ratio between the purple sweet potato flour and soybean epidermis flour for making flakes. This study used a Completely Randomized Design (CRD) with 6 treatments and 3 replications followed by DNMRT test at 5% level. The treatments in this study were F0 (purple sweet potato flour 100%), F1 (purple sweet potato flour and soybean epidermis flour 90:10), F2 (purple sweet potato flour and soybean epidermis flour 80:20), F3 (purple sweet potato flour and soybean epidermis flour 70:30), F4 (purple sweet potato flour and soybean epidermis flour 60:40), and F5 (purple sweet potato flour and soybean epidermis flour 50:50). Results of analysis of variance show that the ratio ratio of purple sweet potato flour and soybean epidermis flour significant by affected the moisture, fat, protein and crude fiber contents, as well as test sensory descriptive and hedonic attributes of taste, aroma and color, but did not significantly influence the texture of descriptive sensory and hedonic test. The best treatment in this study was F3 (purple sweet potato flour and soybean epidermis flour 70:30) with moisture 5,91%, fat 2,09%, protein 5,84%, crude fiber 7,22% and time for crispness in milk 143 seconds. Descriptive sensory test was a little taste of sweet potato, a bit scented sweet potato, purple-brown and slightly crunchy texture, whereas the sensory test by hedonic on taste, aroma, color and texture were somewhat liked by panelists. Keywords: purple sweet potato flour, soybean epidermis flour, flakes